2019
DOI: 10.1111/bcpt.13236
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde perfusion in isolated perfused mouse lungs—Feasibility and effects on cytokine levels and pulmonary oedema formation

Abstract: Retrograde lung vascular perfusion can appear in high‐risk surgeries. The present report is the first to study long‐term retrograde perfusion of isolated perfused mouse lungs (IPLs) and to use the tyrosine kinase ephB4 and its ligand ephrinB2 as potential markers for acute lung injury. Mouse lungs were subjected to anterograde or retrograde perfusion with normal‐pressure ventilation (NV) or high‐pressure ventilation (=overventilation, OV) for 4 hours. Outcome parameters were cytokine, ephrinB2 and ephB4 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…It is possible that the time course of experiments was too short to detect effects on the mRNA expression of PTP1B. EphrinB2 and EphB4 as ligand and consecutive receptors also showed no significant change in expression although ephB4 has been shown to indicate lung injury in mouse IPLs and in vivo [ 26 ]. Differences in those two studies could be due to different infliction of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the time course of experiments was too short to detect effects on the mRNA expression of PTP1B. EphrinB2 and EphB4 as ligand and consecutive receptors also showed no significant change in expression although ephB4 has been shown to indicate lung injury in mouse IPLs and in vivo [ 26 ]. Differences in those two studies could be due to different infliction of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in our study, all rat lungs lasted until the end of the experiments, although edema formation was visible and indicated by lung weight increases in retrograde perfusion. Similar to mouse IPL, there was edema formation in rat IPL with retrograde perfusion in our study, although no second trigger was necessary in contrast to the additional acute lung injury in mouse IPL [ 5 ]. The reported edema formation could also be due to alterations of NO production described for bovine aortic endothelial cells subjected to 180° flow direction change [ 6 ].…”
Section: Discussionmentioning
confidence: 94%
“…However retrograde perfusion was performed with increasing flow rates but only for up to 60 min of perfusion and ventilation [ 4 ]. Another study from our laboratory observed pulmonary edema formation in retrogradely perfused mouse IPL for 4 h only in combination with an additional hit like acute lung injury [ 5 ]. Furthermore, retrograde perfusion led in some mouse IPL to termination of the experiments due to sudden massive pulmonary edema formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations